Inequality in Male and Female Earnings: The Role of Hours and Wages - Doiron, Denise J.; Barrett, Garry F. (The Review of Economics and Statistics, 1996)
The authors decompose annual earnings into hours of work and hourly earnings and analyze male-female differences in earnings inequality using Canadian data. Their results indicate that the larger female inequality in earnings is due to a greater inequality in the distribution of hours of work. The distributions of wages for men and women are either statistically indistinguishable or more equal for women. The authors compare two data points, 1988 and 1981, and find the same structure in the gender comparisons. Also, changes between 1988 and 1981 in earnings inequality are generated from movements in the hours distributions. Copyright 1996 by MIT Press.